Effect of N-methyl deuteration on metabolism and pharmacokinetics of enzalutamide - Jiang J; Pang X; Li L; Dai X; Diao X; Chen X; Zhong D; Wang Y; Chen Y (Dove Medical Press, 2016)
Jinfang Jiang,1,2,* Xuehai Pang,2,3,* Liang Li,1,2 Xiaojian Dai,1,2 Xingxing Diao,1 Xiaoyan Chen,1,2 Dafang Zhong,1,2 Yingwei Wang,2,3 Yuanwei Chen2–4 1State Key Laboratory of Drug Research, Shanghai Institute of Materia Medica, Chinese Academy of Sciences, Shanghai, 2University of Chinese Academy of Sciences, Beijing, 3Chengdu Institute of Organic Chemistry, Chinese Academy of Sciences, 4Hinova Pharmaceuticals Inc, Chengdu, People’s Republic of China *These authors contributed equally to this work Background: The replacement of hydrogen with deuterium invokes a kinetic isotope effect. Thus, this method is an attractive way to slow down the metabolic rate and modulate pharmacokinetics.Purpose: Enzalutamide (ENT) acts as a competitive inhibitor of the androgen receptor and has been approved for the treatment of metastatic castration-resistant prostate cancer by the US Food and Drug Administration in 2012. To attenuate the N-demethylation pathway, hydrogen atoms of the N–CH3 moiety were replaced by the relatively stable isotope deuterium, which showed similar pharmacological activities but exhibited favorable pharmacokinetic properties.Methods: We estimated in vitro and in vivo pharmacokinetic parameters for ENT and its deuterated analog (d3-ENT). For in vitro studies, intrinsic primary isotope effects (KH/KD) were determined by the ratio of intrinsic clearance (CLint) obtained for ENT and d3-ENT. The CLint values were obtained by the substrate depletion method. For in vivo studies, ENT and d3-ENT were orally given to male Sprague Dawley rats separately and simultaneously to assess the disposition and metabolism of them. We also investigated the main metabolic pathway of ENT by comparing the rate of oxidation and hydrolysis in vitro. Results: The in vitro CLint (maximum velocity/Michaelis constant [Vmax/Km]) of d3-ENT in rat and human liver microsomes were 49.7% and 72.9% lower than those of the non-deuterated compound, corresponding to the KH/KD value of ~2. The maximum observed plasma concentration, Cmax, and area under the plasma concentration -time curve from time zero to the last measurable sampling time point (AUC0–t) were 35% and 102% higher than those of ENT when orally administered to rats (10 mg/kg). The exposure of the N-demethyl metabolite M2 was eightfold lower, whereas that of the amide hydrolysis metabolite M1 and other minor metabolites was unchanged. The observed hydrolysis rate of M2 was at least ten times higher than that of ENT and d3-ENT in rat plasma.Conclusion: ENT was mainly metabolized through the “parent→M2→M1” pathway based on in vitro and in vivo elimination behavior. The observed in vitro deuterium isotope effect translated into increased exposure of the deuterated analog in rats. Once the carbon–hydrogen was replaced with carbon–deuterium (C–D) bonds, the major metabolic pathway was retarded because of the relatively stable C–D bonds. The systemic exposure to d3-ENT can increase in humans, so the dose requirements can be reduced appropriately. Keywords: enzalutamide, N-methyl deuteration, deuterium kinetic isotope effect, pharmacokinetics